Ektoplazm.com: Psychedelic trance, internet curation and free music distribution. (31st December 2020) - Charles, Christopher
Abstract : This article looks at the website Ektoplazm.com, which acts as a free distribution service for psychedelic trance music. Ektoplazm is maintained by a single webmaster, DJ Basilisk, who describes the service as a 'curated collection' of music. Basilisk maintains strict aesthetic and technical standards for every item uploaded, helping to create an attractive musical commodity with valuable attributes—albeit one that is offered free of charge. With Ektoplazm as its focal point, this article examines the interaction between curator, community and commodity in the digital era. Here, curation is found to be part of a wider process of reintermediation which adds value to digital music. The stylistic, aesthetic, technical and legal components of Basilisk's curatorial role are considered, and Ektoplazm is placed in the context of psytrance's cultural history, the changing landscape of internet music websites and the free-culture movement.